ASSESSMENT OF BODY DISSATISFACTION IN ADOLESCENTS: EFFECT OF THE WAY OF ADMINISTRATION A SCALE - Baile, José Ignacio; Raich Escursell, Rosa María; Garrido, Emilio (Anales de Psicología / Annals of Psychology, 2003)
The aim of this paper is to discover if the way of administration a subscale of evaluation Body Dissatisfaction (BD), coming from a wider questionnaire, affects to the tendency of answer. In the investigation participated 147 students of secondary school, age between 14 and 17 years, both sexes, they were divided in three conditions of investigation. The first group was administered only the subscale BD of the Eating Disorders Inventory (EDI-2), the second group filled the subscale BD within all inventory EDI-2, and the third group worked with the same subscale mixed with other inventory, the Eating Attitudes Test (EAT-40). The findings show that there are not significant differences in the scores in BD, in three different ways of administration of the same scale. There are different scores between girls and boys in BD, being higher the punctuations of the girls. The confirmation of these findings in other ages and wider samples, it will allow that the investigation of BD through a scale as widespread as this, belong to the EDI, could be used without administering all complete EDI.